Studies in american orchids, v (1962)
While attending the 3rd World Orchid Conference held in London, England, in May 1960, I had the opportunity to study the orchid collections at the leading European Institutions: Royal Botanic Gardens, Kew; British Museum, Natural History Museum, Paris; Delessert Herbarium, Geneva and the Botanical Institute, Madrid. These herbaria contain rich collections of type material many of which represent obscurely known concepts, although they are in an excellent condition for diagnostic purposes.  The following taxonomic notes are mostly based on specimens preserved in the above named Institutions. The majority of the taxa here discussed are part of the Orchid Flora of Colombia and Ecuador, the preparation of which is supported by the National Science Foundation. This assistance of grant-in-aid is gratefully acknowledged.